2011
DOI: 10.1007/s00134-011-2268-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cellular therapy in respiratory diseases

Abstract: A better understanding of the mechanisms that control cell division and differentiation, as well as of their paracrine effects, is required to enable the optimal use of bone marrow-derived stem cell therapy to treat human respiratory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 73 publications
0
42
0
2
Order By: Relevance
“…Whereas some studies on the protective effects of adult stem cells in lung injury have been carried out using bone marrowderived mononuclear cells, including both mesenchymal and hematopoietic stem cells [4][5][6], in this work we focused on MSCs exclusively. We used well-characterised MSCs [15] and applied a number of cells in keeping with the different doses reported in the literature when these stem cells were applied, either intravenously or intratracheally, in rats and mice [10,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas some studies on the protective effects of adult stem cells in lung injury have been carried out using bone marrowderived mononuclear cells, including both mesenchymal and hematopoietic stem cells [4][5][6], in this work we focused on MSCs exclusively. We used well-characterised MSCs [15] and applied a number of cells in keeping with the different doses reported in the literature when these stem cells were applied, either intravenously or intratracheally, in rats and mice [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…One control group was kept under spontaneous breathing for the entire duration of the experiment, while the other three groups of rats were tracheostomised and intubated (cannula 16GA BD Adsyte Pro, Becton Dickinson; Madrid, Spain). Subsequently, one group was kept under spontaneous breathing and the animals from another two groups were subjected to the following interventions: 1) injection of 5610 6 MSCs diluted in 0.3 mL of sterile Dulbecco's phosphate-buffered saline (DPBS) through the penile vein; 2) intratracheal instillation of 0.3 mL of DPBS containing 5610 6 MSCs through the intubation cannula. During the intratracheal instillation experiments, the rats were maintained in a head-up tilted position to prevent MSC spillage.…”
Section: Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the beneficial effects of bone marrow cell therapy in different models of lung injury [5,6,7,8,9,10]. In experimental models of lung fibrosis, bone marrow-derived cells (BMDCs) were able to repair damaged tissue by modulating the inflammatory process and replacing damaged cells [3,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Moreover, the ability of MSCs to home to injured tissues 16 may obviate the need for local delivery strategies, and may result in localized therapeutic benefit after systemic delivery. 17 We wished to determine the efficacy of intratracheal MSC therapy, gain insights into the mechanisms underlying these effects, and compare the efficacy of this approach with that of intravenous MSC therapy. 11 We hypothesized that intratracheal delivery of MSCs would (1) enhance functional recovery and lung repair after VILI; (2) that these effects would be mediated via a paracrine mechanism; and (3) that the efficacy of intratracheal delivery would be similar to intravenous MSC therapy.…”
mentioning
confidence: 99%